05.40: Warping constant equations for hot rolled steel channel sections. (13th September 2017) - Zhang, Ailin; Zhang, Qingfang; Jiang, Ziqin
ABSTRACT: The warping constant is one of the most important section properties for the buckling behaviour of structural members. The formulas for section warping constants are usually based on the middle line mode, and the flange slopes as well as the flange‐to‐web fillets are neglected. In this paper, 32 standard C shapes from the AISC manual were used as examples. They are drawn in AUTOCAD according to their real dimensions, and then the files are imported into ANSYS to calculate the sections' properties. It is found that the warping constants listed in the AISC manual are overestimated by about 26%. Taking the flange slope into account, a new expression of the warping constant for C shapes is presented. After a simple modification, the overestimated margin can be limited to about 5% using this new equation.